Recent Publications (Quarterly Journal of Economics, 1967)
Recent Publications The Quarterly Journal of Economics, Volume 81, Issue 4, November 1967, Pages 707–710, https://doi.org/10.1093/qje/81.4.707 Published: 01 November 1967